2021
DOI: 10.3389/feduc.2021.769573
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Individual Teacher-Child Relationships: An Intervention Study Among Student Teachers in Special Education

Abstract: Relationships with children with special educational needs can be emotionally challenging for teachers and conflicts may negatively impact both children and teachers. Beginning teachers in particular may struggle with negative teacher-child relationships and the emotions these invoke. A first step in coping with relationship difficulties with specific children is increasing the teacher’s awareness and understanding of relational themes and emotions in the relationship with that specific child. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Experimental research provides indications that LLInC enhances teacher sensitivity, selfefficacy beliefs for emotional support, and relationship quality as evidenced by more closeness and less conflict in relationships with children with relational or behavioral problems (Spilt et al, 2012b;Bosman et al, 2021). There is also some evidence that LLInC supports relationships of pre-service teachers with difficult children during internships (Koenen et al, 2021).…”
Section: Second and Third Decadementioning
confidence: 98%
“…Experimental research provides indications that LLInC enhances teacher sensitivity, selfefficacy beliefs for emotional support, and relationship quality as evidenced by more closeness and less conflict in relationships with children with relational or behavioral problems (Spilt et al, 2012b;Bosman et al, 2021). There is also some evidence that LLInC supports relationships of pre-service teachers with difficult children during internships (Koenen et al, 2021).…”
Section: Second and Third Decadementioning
confidence: 98%
“…As teachers often report challenges in establishing high-quality dyadic teacher-student relationships (Jensen et al, 2015;Aspelin et al, 2020;Borremans et al, under review), it is important to note that several intervention studies have demonstrated the potential for enhancing relationship quality (for reviews, see Kincade et al, 2020;Poling et al, 2022). The most noteworthy interventions targeting dyadic teacher-student relationships are Banking Time (and adapted versions;Driscoll and Pianta, 2010;Vancraeyveldt et al, 2015), the Establish-Maintain-Restore (EMR-method Cook et al, 2018;Duong et al, 2019), and LLInC (Leerkracht Leerling Interactie Coaching in Dutch or Teacher Student Interaction Coaching; Spilt et al, 2012;Bosman et al, 2021;Koenen et al, 2021). A common elements analysis revealed several practices, both direct and indirect, that contribute to the effectiveness of these interventions (Kincade et al, 2020).…”
Section: Improving Teacher-student Relationship Qualitymentioning
confidence: 99%
“…As pre-service teachers were found to often rely on maladaptive coping strategies (Gustems-Carnicer et al, 2019) and our results showed that almost half of pre-service teachers do not feel competent in coping with conflicts with students, we argue that teacher education curricula should focus more on teacher well-being in teacher-student relationships and address selfawareness, adaptive coping skills, and self-care. A tool that could be used to this end is the intervention LLInC (Leerkracht Leerling Interactie Coaching in Dutch, or Teacher Student Interaction Coaching; Spilt, 2010-2017), which has recently been applied and evaluated in teacher education (Koenen et al, 2021). LLInC was delivered to pre-service teachers during their final internship in a specialization year of the education program.…”
Section: Differences In Perceived Competence Across Years Of Teacher ...mentioning
confidence: 99%